Differential risks of psoriatic arthritis development in patients with varied psoriasis manifestations: a sex- and ethnicity-specific analysis - Gershater, Bernard; Bieber, Katja; Vorobyev, Artem; Ludwig, Marlene A.; Zirpel, Henner; De Luca, David A.; Thaci, Diamant; Kridin, Khalaf; Ludwig, Ralf J. (Frontiers in Medicine, 2024)
Objectives. This study investigated psoriatic arthritis (PsA) risk across varied psoriasis manifestations, considering sex and ethnicity. Methods. Using TriNetX, a federated database encompassing over 120 million electronic health records (EHRs), we performed global retrospective cohort studies. Psoriasis vulgaris (Pso), pustulosis palmoplantaris (PPP), and generalized pustular psoriasis (GPP) cohorts were retrieved using ICD-10 codes. Propensity score matching, incorporating age, sex, and ethnicity, was employed. An alternative propensity matching model additionally included established PsA risk factors. Results. We retrieved data from 486 (Black or African American-stratified, GPP) to 35,281 (Pso) EHRs from the US Collaborative Network. Significant PsA risk variations emerged: Pso carried the highest risk (hazard ratio [HR] 87.7, confidence interval [CI] 63.4-121.1, p<0.001), followed by GPP (HR 26.8, CI 6.5-110.1, p<0.0001), and PPP (HR 15.3, CI 7.9-29.5, p<0.0001). Moreover, we identified significant sex-and ethnicity-specific disparities in PsA development. For instance, compared to male Pso patients, female Pso patients had an elevated PsA risk (HR 1.1, CI 1.1-1.2, p=0.002). Furthermore, White Pso patients had a higher likelihood of developing PsA compared to their Black or African American counterparts (HR 1.3, p=0.0244). We validated key findings using alternative propensity matching strategies and independent databases. Conclusions.This study delineates nuanced PsA risk profiles across psoriasis forms, highlighting the pivotal roles of sex and ethnicity. Integrating these factors into PsA risk assessments enables tailored monitoring and interventions, potentially impacting psoriasis patient care quality.